Array-based genotyping and expression analysis of barley cv. Maythorpe and Golden Promise - Walia, H.; Wilson, C.; Condamine, P.; Ismail, A.M.; Xu, J.; Cui, X.; Close, T.J. (Springer, 2007)
Golden Promise is a salt-tolerant spring barley closely related to Maythorpe. Salt tolerance in Golden Promise has been attributed to a single mutation at the Ari-e locus (on 5H) resulting from irradiation of Maythorpe. Golden Promise accumulates lower shoot Na+ compared to Maythorpe when growing under saline conditions. This study focused on elucidating the genetic basis and mechanisms involved in this difference.The level of polymorphism between the two genotypes was explored using the Barley1 GeneChip for single feature polymorphisms (SFPs) and an oligonucleotide pool assay for single nucleotide polymorphisms (SNPs). Polymorphism analyses revealed three haplotype blocks spanning 6.4 cM on chromosome 1H, 23.7 cM on chromosome 4H and 3.0 cM on 5H. The Barley1 GeneChip was used to examine transcript abundance in different tissues and stages during development. Several genes within the polymorphic haplotype blocks were differentially regulated. Additionally, a more global difference in the jasmonic acid pathway regulation was detected between the two genotypes.The results confirm that Golden Promise and Maythorpe are genetically very closely related but establish that they are not isogenic, as previously reported, due to three polymorphic haplotype blocks. Transcriptome analysis indicates that the response of the two genotypes to salinity stress is quite different. Additionally, the response to salinity stress in the roots and shoot tissue is strikingly different.